Fertility recovery in sandy soils under bush fallow in southern Mozambique - Nhantumbo, Alfredo Bernardino Julio Da Costa (University of the Free State, 2008)
Bush fallow under shifting cultivation is the most common practised subsistence farming system in southern Mozambique. This system is likely to persist due to the existence of large areas sparsely inhabited coupled with financial limitations preventing small scale farmers from buying fertilizers. The bush fallow is intended to recover naturally the productive capacities of soils lost during cropping. This study was conducted therefore to gain a better understanding on the composition and biomass of bush fallow vegetation, climatic factors affecting leaf litter decay of an important tree species and the dynamics of some soil fertility indicators. Five agroecosystems representing rainfall regions of <400 mm (AE6), 400-600 mm (AE5), 600-800 mm (AE3), 800-1000 mm (AE2), >1000 mm (AE1) and a transitional agroecosystem of 400-800 mm (AE4) were selected. Within each agroecosystem, five land uses (virgin, cultivated, < 5 years fallow, 5-15 years fallow and >15 years fallow) were identified. Descriptions and comparisons of vegetation were performed between land uses within agroecosystems and similar land uses across agroecosystems, except in cultivated land; effects of soil water content and soil temperature on decomposition of Brachystegia spiciformis leaf litter were evaluated in recently abandoned agricultural fields cleared of any vegetation (Bare) and in >15 years fallow fields (15F) at sites in a transect that covered AE2 to AE6; and at every combination of agroecosystem and land use the dynamics of organic C, total N, CEC, pH, P, Ca, Mg and K were determined in the 0-50 mm, 50-100 mm and 100-200 mm soil layers. A total of 204 species that including N-fixing species, belonging to 141 genera and 50 families divided into tree, shrub and herbaceous layers were identified. The tree layer was only found in virgin fields and in fields abandoned to bush fallow >15 years, whereas shrub and herbaceous layers occurred in all fields. The tree species in bush fallow fields of coastal and wetter AE1, AE2 and AE3 (dominated by B. spiciformis and Julbernaldia globiflora) outnumber those in inland and drier AE4, AE5 and AE6 (dominated by Birchemia discolour and Colophospermum mopane) and have larger diameter that result in greater biomass. Number of shrubs decreased from coastal an wetter to inland and drier agroecosystems. The herbaceous biomass declined from young to old fallow fields in coastal and wetter agroecosystems, while the converse was observed in inland and drier agroecosystems. Nitrogen-fixing species tended to occur more in bush fallow fields older than 15 years. In inland and drier agroecosystems the tree biomass in 15F fields tended to be higher than in virgin fields due to presence of succession species that differ from the original ones. In the wetter agroecosystems C loss from B. spiciformis leaf litter was faster, whereas in the drier ones it was more sensitive to rainfall pulses. Similarly, C loss was faster in 15F fields than in bare fields. In coastal and wetter AE1, AE2 and AE3 there was a declining trend in organic C and total N from virgin to cultivated fields. This trend proceeds to the <5 years fallow fields and thereafter the contents of the two indicators increased in older fallow fields. A different pattern was found in the dry AE4 and AE5 where organic C and total N tended to decline gradually even with longer fallow periods. In the severely dry AE6 no clear trend was found. The pH in all agroecosystems decreased from cultivated to fallow fields, an effect attributable to a gradual decrease in the basic cations released on the soil surface by the ash produced during slash and burn. A slight increase in the silt plus clay fraction from AE4 to AE5 was found, which resulted in increased CEC, P, Ca, Mg and K. From the coastal and wetter to inland and drier agroecosystems pH, P and Ca increased, except in AE4 and AE5, which had lower pH and Ca values. The lower values of pH resulted in lower contents of P in AE4 and Ca and Mg in both agroecosystems, which have the same vegetation, suggesting that this should be the determining factor. The results from this study showed that a bush fallow period of longer than 15 years is required for restoration of soil fertility in abandoned cultivated fields to the same level as in virgin fields. This aspect must be taken into account when strategies are developed to improve the sustainability of cropping on the sandy soils of southern Mozambique.

Bosbraak onder verskuiwende verbouing is die mees algemene bestaansboererystelsel wat in suidelike Mosambiek toegepas word. Die stelsel sal waarskynlik voortgaan weens die groot ylbevolkte areas en kleinboere se beperkte finansiële vermoëns om kunsmis te koop. Die bosbraak het ten doel om die produksievermoë van gronde, wat met gewasverbouing verlore gaan, natuurlik te herstel. Hierdie studie is dus gedoen om ‘n beter begrip te kry van die samestelling en biomassa van bosbraakplantegroei, klimaatfaktore wat die afbraak van ‘n belangrike boomspesie beïnvloed en die dinamika van sekere grondvrugbaarheidsindikatore. Vyf agro-ekosisteme wat reënvalstreke van <400 mm (AE6), 400-600 mm (AE5), 600- 800 mm (AE3), 800-1000 mm (AE2) en >1000 mm (AE1) en ‘n oorgangsagroekosisteem van 400-800 mm (AE4) is geselekteer. Binne elke agro-ekosisteem is vyf landsgebruike (onversteurde, bewerkte, <5 jaar braak, 5-15 jaar braak en >15 jaar braak) geïdentifiseer. Beskrywings en vergelykings van die plantegroei tussen landgebruike binne agro-ekosisteme en soortgelyke landgebruike oor agro-ekosisteme is gedoen; effekte van grondwaterinhoud en grondtemperatuur op die afbraak van Brachystecia spiciformis blaarreste is in bewerkte lande sonder enige plantegroei en wat onlangs vir bosbraak gelos is (Kaal), en in >15 jaar braaklande (>15F) by lokaliteite wat ‘n deursnit vanaf AE2 tot AE6 dek, geëvalueer; en by elke kombinasie van agroekosisteem en landgebruik is die dinamika van organiese C, totale N, KUK, pH, P, Ca, Mg en K in die 0-50 mm, 50-100 mm en 100-200 mm grondlae bepaal. ‘n Totaal van 204 spesies wat N-bindende spesies in sluit en tot 141 genera en 50 families behoort, is geïdentifiseer en in ‘n boom-, struik- en kruidlaag verdeel. Die boomlaag is slegs in onbewerkte en >15 jaar bosbraaklande gevind, terwyl die struiken kruidlae in alle lande voorkom. Die boomspesies in bosbraaklande van die kus en natter AE1, AE2 en AE3 (gedomineer deur B. Spiciformis and Julbernaldia globiflora) is meer as die in binnelandse en droër AE4, AE5 en AE6 (gedomineer deur Birchemia discolour en Colophospermum mopane) en het ‘n groter diameter en dus meer biomassa. Die aantal struike neem vanaf die kus en natter na die binnelandse en droër agro-ekosisteme af. Die kruidbiomassa neem af van die jong na ou braaklande in die kus en natter agro-ekosisteme en die omgekeerde is in die binnelandse en droër agroekosisteme waargeneem. Stikstofbindende spesies neig om meer in bosbraaklande ouer as 15 jaar te wees. In die binnelandse en droër agro-ekosisteme neig die boombiomassa in die 15F lande om hoër te wees as in die onversteurde lande weens die teenwoordigheid van opvolgspesies wat verskil van die oorspronklikes. In die natter agro-ekosisteme was die verlies van C uit B. spiciformis blaarreste vinniger terwyl in die droër sisteme was dit meer sensitief vir reënvalbuie. Soortgelyk was koolstofverlies vinniger in die 15F lande as in die kaal lande. In die kus en natter AE1, AE2 en AE3 is daar ‘n neiging dat organiese C en totale N vanaf onversteurde na bewerkte lande afneem. Hierdie neiging duur voort in die >5 jaar braaklande en daarna neem die inhoud van die twee indikatore toe in die ouer braaklande. ‘n Ander patroon is in die droë AE4 en AE5 gevind waar organiese C en totale N neig om geleidelik af te neem met selfs langer braak periodes. In die baie droë AE6 was daar geen duidelike patroon. Die pH in alle agro-ekosisteme het afgeneem vanaf bewerkte na braaklande en die effek word toegeskryf aan die geleidelike afname in die basiese katione wat deur die as afkomstig van kap en brand op die grondoppervlak vrygestel is. ‘n Effense toename in die slik plus klei fraksie van AE4 na AE5 is gevind wat ‘n toename in KUK, P, Ca, Mg en K tot gevolg het. Vanaf die kus en natter na binnelandse en droër agro-ekosisteme het pH, P en Ca toegeneem, behalwe in AE4 en AE5 wat laer pH en Ca waardes gehad het. Die laer waardes van pH het tot laer inhoude van P in AE4 en Ca en Mg in beide agro-ekosisteme gelei wat dieselfde plantegroei het en die is moontlik die bepalende faktor. Die resultate van hierdie studie het getoon dat ‘n bosbraak periode van langer as 15 jaar nodig is om die grondvrugbaarheid van verlate bewerkte lande tot dieselfde vlak as die van onversteurde lande te verhoog. Hierdie aspek moet in berekening gebring word wanneer strategieë ontwikkel word om die volhoubaarheid van gewasverbouing op die sanderige gronde van suidelike Mosambiek te verbeter.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2008
Keywords: Agroecosystem; Ecological importance; Exchangeable bases; Organic matter; Shifting cultivation; Vegetation composition; Fallowing -- Mozambique; Sustainable agriculture -- Mozambique; Soil fertility -- Mozambique